Analisis Faktor-Faktor yang Mempengaruhi Kemiskinan Kota Bogor Tahun 2002 - 2013 - Nisa, Khairun; , Dr. Daryono Soebagyo, M.Ec (2016)
This research entitled "Analysis of the Factors that Influence the Poverty of Bogor City in 2002-2013". This research aims to analyze and determine how much the influence of economic growth, unemployment, education, household consumption, household saving, against poverty of Bogor City in 2002-2013. This research uses secondary data such as time series data in 2002 - 2013, that is data on poverty, economic growth, unemployment, education, household consumption, and household saving. The analytical method used is Ordinary Least Square (OLS). Based on the analysis, showed that economic growth impact negative and significant effect on the poverty. At the same time, education impact negative and not significant effect on poverty. For employment and household saving, affect positive and not significant effect on poverty. Here after, household consumption impact positive and significant effect on poverty. Therefore, the government should expand employment opportunities followed by an increasing number of labor force. Waive education fees in any form.